Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2174/1871530320666200821155756
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Represses the Aggressive Potential of Osteosarcoma

Abstract: Background: Osteosarcoma (OS) is the basic bone neoplasm with lower survival and poor prognosis. It is distinguished by its offensive nature and metastatic potential. The fundamental death source in OS patients is lung metastasis. In addition, the proliferation and cell migration are thus essential for cancer progression, especially for intrusion and transformation. Several studies have illustrated that 1,25-Dihydroxyvitamin D (1,25(OH)2D) has a critical role in the growth and differentiation of bone. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These antiproliferative effects of vitamin D on osteosarcoma cell lines were only recently confirmed in a different study (115). Moreover, recent findings suggest that 1,25D treatment of osteosarcoma cells results in decreased cell proliferation, migration an invasiveness, thus, reducing the aggressive potential of osteosarcoma cells (116). Furthermore, we have recently demonstrated that the VDR itself, and independent of its ligand has a critical function in controlling cancer cell behaviour in bone and cancer metastasis to bone (117,118).…”
Section: Vitamin D In Bone Oncologymentioning
confidence: 88%
“…These antiproliferative effects of vitamin D on osteosarcoma cell lines were only recently confirmed in a different study (115). Moreover, recent findings suggest that 1,25D treatment of osteosarcoma cells results in decreased cell proliferation, migration an invasiveness, thus, reducing the aggressive potential of osteosarcoma cells (116). Furthermore, we have recently demonstrated that the VDR itself, and independent of its ligand has a critical function in controlling cancer cell behaviour in bone and cancer metastasis to bone (117,118).…”
Section: Vitamin D In Bone Oncologymentioning
confidence: 88%
“…VD3 and its analogs, such as osteosarcoma cell lines MG-63 and SaOS2, also promote osteoblast differentiation. P73 is essential for VD3-mediated osteosarcoma differentiation, and induction of p73 in response to DNA damage enhances VD3-mediated osteosarcoma cell line differentiation [ 115 , 116 , 117 , 118 , 119 , 120 ].…”
Section: Multiple Myeloma (Mm) and Osteosarcomamentioning
confidence: 99%
“…25(OH)D is further hydroxylated in the kidneys or within specialized cell types by 25(OH)D-1-OHase (CYP27B1) to produce 1-alpha, 25-dihydroxyvitamin D (also known as 1,25(OH)2D), the biologically active derivative of vitamin D 29,[39][40][41][42][43] . The 1,25(OH)2D effects are mediated by the vitamin D receptor (VDR), an intracellular nuclear receptor superfamily member, that can promote cell cycle arrest and apoptosis via post-transcriptional and gene regulatory means 39,[44][45][46][47][48][49][50][51][52][53][54] . In mammals, the physiological and molecular effects of vitamin D3 on bone health and function have been experimentally and clinically validated 29 .…”
Section: Introductionmentioning
confidence: 99%